1998
DOI: 10.1111/j.1469-7793.1998.031br.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of chloride secretion across porcine endometrial epithelial cells by prostaglandin E2

Abstract: The objective of this study was to investigate the mechanism of PGE2 regulation of Cl− transport across glandular endometrial cells grown in primary culture. Most of the basal short circuit current (Isc) was inhibited by luminal addition of 5‐nitro‐2‐(3‐phenylpropylamino)benzoic acid (NPPB) or glibenclamide, suggesting the presence of a basally active Cl− conductance in the apical membrane. Basolateral addition of 10 μM PGE2 increased Isc by 41 ± 3 μA. A similar response was observed when cells were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 41 publications
4
46
0
Order By: Relevance
“…Although this result appears to be consistent with the suggested model above it is important to note that DIDS also blocks certain types of Cl -channels, thus more direct methods will be required to establish the mechanism of HCO 3 -secretion in this epithelium. Stimulation of Cl -secretion by 8-cpt cAMP was previously reported in cultured mammalian endometrial epithelial cells (Deachapunya and O'Grady, 1998). However, native porcine endometrial tissues mounted in Ussing chambers and treated with 8-cpt cAMP or with PGF2α, produced a sustained increase in amiloride-sensitive Na + absorption (Vetter and O'Grady, 1996;Vetter et al, 1997).…”
Section: Discussionmentioning
confidence: 97%
“…Although this result appears to be consistent with the suggested model above it is important to note that DIDS also blocks certain types of Cl -channels, thus more direct methods will be required to establish the mechanism of HCO 3 -secretion in this epithelium. Stimulation of Cl -secretion by 8-cpt cAMP was previously reported in cultured mammalian endometrial epithelial cells (Deachapunya and O'Grady, 1998). However, native porcine endometrial tissues mounted in Ussing chambers and treated with 8-cpt cAMP or with PGF2α, produced a sustained increase in amiloride-sensitive Na + absorption (Vetter and O'Grady, 1996;Vetter et al, 1997).…”
Section: Discussionmentioning
confidence: 97%
“…5). Deachapunya and O'Grady suggested that PGE 2 activates adenylyl cyclase in cultured endometrial epithelial cells, resulting in an increase in intracellular cAMP (11). Other reports showed that there are four PGE 2 receptors (EPs), designated EP1, EP2, EP3, and EP4, and that PGE 2 stimulates the production of cAMP via EP2 and EP4 receptors linked to the Gs protein (4,31).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the intracellular cAMP activates CFTR Cl Ϫ channels through protein phosphorylation mediated by PKA (11). We previously found that hemolysin activates the cAMP-dependent Cl Ϫ secretory pathway, which is related to CFTR, in Caco-2 cells (a human colonic epithelial cell line) (39).…”
Section: Discussionmentioning
confidence: 99%
“…20 To maintain charge balance in the lumen, sodium ions (cations) are pulled across the epithelium, also drawing water molecules and thus causing diarrhea. 19 PGE 2 is a potent colonic epithelial chloride ion secretagogue [21][22][23] ; however, it is not known whether it induces sodium ion flux across the epithelium. Colonic epithelial tight junctions (TJs) act as an important barrier for paracellular movement of macromolecules and ions across the epithelium.…”
mentioning
confidence: 99%